2015
DOI: 10.1038/srep13799
|View full text |Cite
|
Sign up to set email alerts
|

Water use efficiency of China’s terrestrial ecosystems and responses to drought

Abstract: Water use efficiency (WUE) measures the trade-off between carbon gain and water loss of terrestrial ecosystems, and better understanding its dynamics and controlling factors is essential for predicting ecosystem responses to climate change. We assessed the magnitude, spatial patterns, and trends of WUE of China’s terrestrial ecosystems and its responses to drought using a process-based ecosystem model. During the period from 2000 to 2011, the national average annual WUE (net primary productivity (NPP)/evapotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
135
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(159 citation statements)
references
References 54 publications
20
135
1
3
Order By: Relevance
“…Additionally, elevated CO 2 and climate change can also execrate impacts on hydrological and ecosystem productivity through changing water use efficiency (Miller-Rushing et al, 2009;de Kauwe et al, 2013;Zhang, F. et al, 2014;Liu et al, 2015) and vegetation processes (e.g., stomatal conductance and LAI; Sun et al, 2014). However, the WaSSI model did not consider these effects, potentially resulting in errors in estimating ET, GPP, or water yield (Cox et al, 2000;Gedney et al, 2006;Oki and Kanae, 2006;Betts et al, 2007;Piao et al, 2007).…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Additionally, elevated CO 2 and climate change can also execrate impacts on hydrological and ecosystem productivity through changing water use efficiency (Miller-Rushing et al, 2009;de Kauwe et al, 2013;Zhang, F. et al, 2014;Liu et al, 2015) and vegetation processes (e.g., stomatal conductance and LAI; Sun et al, 2014). However, the WaSSI model did not consider these effects, potentially resulting in errors in estimating ET, GPP, or water yield (Cox et al, 2000;Gedney et al, 2006;Oki and Kanae, 2006;Betts et al, 2007;Piao et al, 2007).…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Hence, models and tools need to be dynamic and account for varying land uses, species and structure [69], and disturbances at fine spatial (e.g., tree) and temporal (e.g., storm event) scales. Empirical rainfall-runoff models built from historical data may not be applicable under future climate change conditions when plant growing season length, forest structure and species composition, and plant water use efficiency [70] have changed over time.…”
Section: Challenges To Existing Best Management Practices (Bmps) and mentioning
confidence: 99%
“…Water use efficiency is recognized as an important characteristic of productivity in various natural scientific disciplines and has been used recently at the ecosystem level [8,16,[47][48][49][50][51]. Ecologists commonly use the ratio of ecosystem fluxes such as NPP [8,16,52], net ecosystem productivity/exchange (NEP/NEE) [49,50], or gross primary productivity (GPP) [48] to water loss (ET or transpiration; [19,48,53] as a measure of WUE.…”
Section: Ecosystem Water Use Efficiencymentioning
confidence: 99%
“…Studies have shown that WUE increases with aridity [8,[11][12][13][14][15][16][17] and that water limited ecosystems tend to have higher WUE [11,12,18]. Across all systems, if a drought becomes severe enough, a breakdown in ecosystem resistance can lead to a reduction in WUE [8,14,15,17,19] and ecosystem type conversions [8,17].…”
Section: Introductionmentioning
confidence: 99%